Analisis Sistem Pelayanan Komplain Air Dalam Upaya Peningkatan Kualitas Kinerja PERUMDA Tirtanadi Cabang Sei Agul - Manurung, Nabila Tasya Nurhafifah; Rahmani, Nur Ahmadi Bi (Jurnal Informatika, 2023)
The motivation behind this research is to find out how clean water dispersion is carried out by the Regional Drinking Water Organization (PDAM Tirtanadi) in Medan Cab Sei Agul City. To find out the supporting and inhibiting elements in the implementation of clean water dissemination organizations (PERUMDA Tirtanadi) Medan Cab sei agul. The distribution of clean water at PERUMDA Tirtanadi Cab Sei Agul in Medan City has made great efforts to improve administrative standards by supplying clean water to customers, as seen from the many exhibitions that have been held to check or repair the damage. took place in the city of Medan. Flow can be managed skillfully and comprehensively. Likewise, there are obstacles in offering the type of assistance and reactions from workers in dealing with problems in the field, which means building how much water is created with the aim that all PERUMDA Tirtanadi clients' needs can be metideally.